PENEGAKAN DAN PENERAPAN HUKUM WAKAF - Hosen, Nadratuzzaman (Islamic Economics and Business Faculty of UIN Antasari, 2015)
Abstract: This paper discusses about law of waqf implementation in Indonesia. Regulations endow-ments have been proposed by the Government and approved by the legislature to form Undang-UndangNomor 41 Tahun 2004 about Waqf, which is complemented by the executive to establish and enforcePeraturan Pemerintah Nomor 42 Tahun 2006 about the implementation of Undang-Undang Nomor41 Tahun 2004. Implementation of the law has been prepared by forming Indonesian Waqf Board(BWI), and the Deed of Pledge Officer waqf (PPAIW) located in the Office of Religious Affairs, andIndonesian Ulema Council (MUI). In terms of cash waqf, also formed Islamic Financial InstitutionsRecipients Endowments money (LKS-PWU) to facilitate development cash waqf. For law enforcement,waqf was created as one of the absolute competence religious courts based on the examination andsettlement of formal law. From this effort, waqf management was expected to run well in accordancewith the laws in the set.